2011
DOI: 10.1016/j.psychres.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Ecologically valid support for the link between cognitive and psychosocial functioning in bipolar disorder

Abstract: Prior research into the link between cognitive and psychosocial functioning in bipolar disorder has examined primarily asymptomatic patients, has measured these domains concurrently, and has failed to establish convergent validity in the assessment of psychosocial dysfunction. The present study examines the relation between cognitive and psychosocial functioning at the time of discharge from hospitalization for acute mood disturbance. We obtained measures of psychosocial functioning that were both close and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…This concept refers to the degree to which classical neuropsychological tests are empirically related to measures of every‐day functioning. Thus, even though the tests used in this report are not designed with ‘ecological validity’ in mind, they may still be predictive of everyday functioning, as reported in several studies (51, 56–58).…”
Section: Discussionmentioning
confidence: 95%
“…This concept refers to the degree to which classical neuropsychological tests are empirically related to measures of every‐day functioning. Thus, even though the tests used in this report are not designed with ‘ecological validity’ in mind, they may still be predictive of everyday functioning, as reported in several studies (51, 56–58).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, no associations were observed between cognitive performance and general function assessed with the GAF scale in depressed patients with BD (25). Studies that assessed patients in additional mood states (mania, hypomania) found that executive function (34,35), verbal learning, verbal memory (35) and attention (34) were related to poorer general function (GAF) across all mood states. In a single cross-sectional study on cognitive performance and general functioning, mood states (depressed, manic, euthymic) were assessed at multiple time points over 30 months in 25 patients with BD (24).…”
Section: Measures Of General Functional Impairmentmentioning
confidence: 89%
“…When social and occupational functioning were assessed, it was found that processing speed correlated positively with social function and verbal learning with occupational function across different mood states in patients with BD, which indicates an association between cognitive and social/ occupational function independent of mood states (33). Moreover, a higher likelihood of disability was observed in association with poorer performance in verbal memory, executive function and attention across all mood states (34).…”
Section: Measures Of General Functional Impairmentmentioning
confidence: 93%
See 1 more Smart Citation
“…It is well known that cognition is compromised in individuals with BD, and that cognitive deficits contribute to the high levels of functional and psychosocial impairment associated with this disorder .…”
Section: The Bipolar Suicidality Model (Bsm)mentioning
confidence: 99%